Stars of fortune [compact disc, unabridged] - Roberts, Nora (Roberts, Nora. Guardians trilogy., 2015)
Centuries after guardian stars tied to the powers of fire, ice, and water fall to earth and place the fates of worlds in the hands of their finders, reclusive artist Sasha Riggs is drawn by vivid dreams to a Greek island to search for the fire star and passion.